Frege a Wittgenstein. Uwagi o fiasku korespondencyjnego dialogu - Rygalski, Andrzej (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2010)
The letters that were found after years are the evidence of hard intellectual work that had been conducted under very infavourable conditions. They refer to the time when Wittgenstein was writing "Tractatus" while Frege was working on his articles "Thought" and "Negation". Correspondence between Frege and Wittgenstein prove the common will of communication and mutual understanding. Thus remains the question why those two close and well known to each other thinkers have not realized that willingness.